The ncRNA-mediated regulatory networks of defensins and lysozymes in Riptortus pedestris: involvement in response to gut bacterial disturbances - Ren, Yipeng; Fu, Siying; Dong, Wenhao; Chen, Juhong; Xue, Huaijun; Bu, Wenjun (Frontiers in Microbiology, 2024)
Insects depend on humoral immunity against intruders through the secretion of antimicrobial peptides (AMPs) and immune effectors via NF-κB transcription factors, and their fitness is improved by gut bacterial microbiota. Although there are growing numbers of reports on noncoding RNAs (ncRNAs) involving in immune responses against pathogens, comprehensive studies of ncRNA-AMP regulatory networks in Riptortus pedestris, which is one of the widely distributed pests in East Asia, are still not well understood under feeding environmental changes. The objective of this study employed the whole-transcriptome sequencing (WTS) to systematically identify the lncRNAs (long noncoding RNA) and circRNAs (circular RNA) and to obtain their differential expression from the R. pedestris gut under different feeding conditions. Functional annotation indicated that they were mainly enriched in various biological processes with the GO and KEGG databases, especially in immune signaling pathways. Five defensin (four novel members) and eleven lysozyme (nine novel members) family genes were identified and characterized from WTS data, and meanwhile, phylogenetic analysis confirmed their classification. Subsequently, the miRNA-mRNA interaction network of above two AMPs and lncRNA-involved ceRNA (competing endogenous RNA) regulatory network of one lysozyme were predicted and built based on bioinformatic prediction and calculation, and the expression patterns of differentially expressed (DE) defensins, and DE lysozymes and related DE ncRNAs were estimated and selected among all the comparison groups.Finally, to integrate the analyses of WTS and previous 16S rRNA amplicon sequencing, we conducted the Pearson correlation analysis to reveal the significantly positive or negative correlation between above DE AMPs and ncRNAs, as well as most changes in the gut bacterial microbiota at the genus level of R. pedestris. Taken together, the present observations provide great insights into the ncRNA regulatory networks of AMPs in response to rearing environmental changes in insects and uncover new potential strategies for pest control in the future.